Global perspectives on dissociative disorders : individual and societal oppression - Sar, Vedat; Middleton, Warwick; Dorahy, Martin J., 1971- (London : Routledge, 2014)
Dissociative disorders are one of the psychiatric consequences of childhood psychological trauma. While oppression is an aspect of traumatic conditions, dissociation undermines resistance to oppression throughout a person's lifespan. Neither oppression nor dissociation are restricted to particular cultures, and both can affect the individual as well as societies. This collection engages with the universality of dissociative disorders and their close relationship to oppression. The chapters cover extreme examples such as ongoing incest in adulthood, children and adults forced to kill others, and abusive states in interrogation. Further subjects examined include the utilization of dissociation in postmodern societies to maintain oppression, the oppressive conditions of asylum seekers and the consequences of oppression as they are dealt with in psychotherapy. The final chapter considers how a paedophile pandering network employed multi-layered oppression to prevent the public becoming aware of the widespread and organised abuse of children.
Contents note continued: 9. Boundary Modifications in the Treatment of People with Dissociative Disorders: An International Perspective / Adah Sachs -- 10. Seeking Asylum---Trauma, Mental Health, and Human Rights: An Australian Perspective / Louise Newman -- 11. The Franklin Scandal: The Cover-Up of Child Abuse and its Analogues to Dissociative Identity Disorder / Nick Bryant.
Includes bibliographical references and index.
Keywords: Psychic trauma; Dissociation (Psychology).; Oppression (Psychology).; Dissociative disorders